Direct visualization of hemolymph flow in the heart of a grasshopper (Schistocerca americana) - Lee, Wah-Keat (BioMed Central, 2009)
BACKGROUND: Hemolymph flow patterns in opaque insects have never been directly visualized due to the lack of an appropriate imaging technique. The required spatial and temporal resolutions, together with the lack of contrast between the hemolymph and the surrounding soft tissue, are major challenges. Previously, indirect techniques have been used to infer insect heart motion and hemolymph flow, but such methods fail to reveal fine-scale kinematics of heartbeat and details of intra-heart flow patterns. RESULTS: With the use of microbubbles as high contrast tracer particles, we directly visualized hemolymph flow in a grasshopper (Schistocerca americana) using synchrotron x-ray phase-contrast imaging. In-vivo intra-heart flow patterns and the relationship between respiratory (tracheae and air sacs) and circulatory (heart) systems were directly observed for the first time. CONCLUSION: Synchrotron x-ray phase contrast imaging is the only generally applicable technique that has the necessary spatial, temporal resolutions and sensitivity to directly visualize heart dynamics and flow patterns inside opaque animals. This technique has the potential to illuminate many long-standing questions regarding small animal circulation, encompassing topics such as retrograde heart flow in some insects and the development of flow in embryonic vertebrates.